Properties of galaxies with an offset between the position angles of the major kinematic and photometric axes - Pilyugin, Leonid S.; Grebel, Eva K.; Zinchenko, Igor A. (Astronomy and astrophysics, 2020)
We derive the photometric, kinematic, and abundance characteristics of 18 star-forming MaNGA galaxies with fairly regular velocity fields and surface brightness distributions and with a large offset between the measured position angles of the major kinematic and photometric axes, ΔPA ≳ 20°. The aim is to examine if there is any other distinctive characteristic common to these galaxies. We found morphological signs of interaction in some (in 11 out of 18) but not in all galaxies. The observed velocity fields show a large variety; the maps of the isovelocities vary from an hourglass-like appearance to a set of straight lines. The position angles of the major kinematic axes of the stellar and gas rotations are close to each other. The values of the central oxygen abundance, radial abundance gradient, and star formation rate are distributed within the intervals defined by galaxies with small (no) ΔPA of similar mass. Thus, we do not find any specific characteristic common to all galaxies with large ΔPA. Instead, the properties of these galaxies are similar to those of galaxies with small (no) ΔPA. This suggests that either the reason responsible for the large ΔPA does not influence other characteristics or the galaxies with large ΔPA do not share a common origin, they can, instead, originate through different channels.
Gesehen am 14.02.2020